Simultaneous validation of the SunTech CT40 automated blood pressure measurement device by the 1993 British Hypertension Society protocol and the Association for the Advancement of Medical Instrumentation/International Organization for Standardization 81060-2: 2013 standard. Issue 5 (October 2017) - Polo Friz, Hernan; Punzi, Veronica; Petri, Francesco; Orlandi, Riccardo; Maggiolini, Daniele; Polo Friz, Melisa; Primitz, Laura; Vighi, Giuseppe
Abstract : Objective: This study aimed to perform a simultaneous, third-party, independent validation of the oscillometric SunTech CT40 device for blood pressure (BP) measurement, according to the 1993 protocol of the British Hypertension Society and the standard of the Association for the Advancement of Medical Instrumentation (AAMI)/the International Organization for Standardization (ISO) 81060-2:2013. Participants and methods: Patient recruitment, study procedures, and data analysis followed the recommendations stated by the protocols. The study was approved by the institutional review board. Results: A total of 94 participants were included, 52 (55.3%) women, mean±SD age: 63.1±18.0 years, mean±SD arm circumference: 35.0±9.0 cm. The average of observers' entry BPs was 146.9±37.2 mmHg for systolic blood pressure (SBP) and 82.2±22.1 mmHg for diastolic blood pressure (DBP). Differences between the standard measurement and the test device within 5, 10, and 15 mmHg, for the better observer, were 79.4, 96.5, and 100.0% for SBP and 82.6, 97.5, and 100.0% for DBP, respectively. The mean±SD differences between the readings obtained using the test device and those obtained by the observers (AAMI/ISO 81060-2:2013 standard criterion 1) were 0.3±5.0 mmHg (SBP) and −0.8±4.3 mmHg (DBP), and the mean±SD differences between average of reference readings and average of test device readings in each patient (criterion 2) were 0.3±3.9 and −0.8±3.5 mmHg for SBP and DBP, respectively. Conclusion: The CT40 BP device achieved A/A grade of the British Hypertension Society protocol and fulfilled the requirements (criteria 1 and 2) of the AAMI/ISO standard. CT40 can be recommended for BP measurement in adults.